Establishment of Monitoring Methods for Autophagy in Rice Reveals Autophagic Recycling of Chloroplasts and Root Plastids during Energy Limitation. Issue 4 (25th February 2015) - Izumi, Masanori; Hidema, Jun; Wada, Shinya; Kondo, Eri; Kurusu, Takamitsu; Kuchitsu, Kazuyuki; Makino, Amane; Ishida, Hiroyuki
Abstract : Autophagy is responsible for the degradation of leaf chloroplasts and root plastids in rice plants and functions during energy limitation caused by interruption of photosynthesis. Abstract: Autophagy is an intracellular process leading to vacuolar or lysosomal degradation of cytoplasmic components in eukaryotes. Establishment of proper methods to monitor autophagy was a key step in uncovering its role in organisms, such as yeast ( Saccharomyces cerevisiae ), mammals, and Arabidopsis ( Arabidopsis thaliana ), in which chloroplastic proteins were found to be recycled by autophagy. Chloroplast recycling has been predicted to function in nutrient remobilization for growing organs or grain filling in cereal crops. Here, to develop our understanding of autophagy in cereals, we established monitoring methods for chloroplast autophagy in rice ( Oryza sativa ). We generated transgenic rice-expressing fluorescent protein (FP) OsAuTophaGy8 (OsATG8) fusions as autophagy markers. FP-ATG8 signals were delivered into the vacuolar lumen in living cells of roots and leaves mainly as vesicles corresponding to autophagic bodies. This phenomenon was not observed upon the addition of wortmannin, an inhibitor of autophagy, or in an ATG7 knockout mutant. Markers for the chloroplast stroma, stromal FP, and FP-labeled Rubisco were delivered by a type of autophagic body called the Rubisco-containing body (RCB ) in the same manner. RCB production in excised leaves was suppressed by supply of external sucrose or light. The release of free FP caused by autophagy-dependent breakdown of FP-labeled Rubisco was induced during accelerated senescence in individually darkened leaves. In roots, nongreen plastids underwent both RCB -mediated and entire organelle types of autophagy. Therefore, our newly developed methods to monitor autophagy directly showed autophagic degradation of leaf chloroplasts and root plastids in rice plants and its induction during energy limitation.